Proposta de boas práticas de armazenamento e manuseio de óleos lubrificante - Campos Junior, Ademir de (2017)
The precautions taken in the deposits of the distribution companies have the purpose of providing the consumer with higher quality products. These precautions include systematic quality control throughout the lubricant manufacturing process, packaging and packaging, to prevent contamination and other damages that could compromise product quality. Thus the importance of storing the lubricants properly is due to the need to extend the life of the equipment without contamination of the machines. Care must be taken with lubricating oils during all processes ranging from strict quality control throughout the entire lubricant manufacturing process to proper final disposal. It should be noted that such care is necessary since when used in equipment, it avoids contaminations and other damages that could compromise the quality and characteristics of the product. One of the main failures of the equipment in the industries is related to the lubrication, therefore one must seek better practices of handling and storage of these oils. Many industries store and handle lubricating oils improperly, which can lead to equipment damage. Contamination of the lubricant causes its physical and chemical properties to be altered and causes premature wear of the mechanical component. In the long run, this wear can lead to component breakage, resulting in machine downtime and operational loss. All lubrication tasks must be organized and planned to run with the correct lubricant, in the right amount and using the correct procedures. The accomplishment of the present work made possible to deepen the studies on the storage and the handling of the lubricants in the industries. In this logic, this study had as objective to make a proposal of good practices of storage and handling of lubricating oils in a company of the steel industry. It was demonstrated through a flowchart the steps in which the lubricating oils pass, it was suggested to make a new lubricant room, it presents through a low plant defining the lay out of the proposed room. The Company was presented with such a proposal defining the new lay out of the room, placing it in the order required in the quality standard, with all the advantages that this new methodology offers.